Response to vitamin D and depression in geriatric primary care patients - Muc-Wierzgoń M (Dove Medical Press, 2013)
Malgorzata Muc-Wierzgon, Ewa Nowakowska-Zajdel, Katarzyna Klakla, Sylwia Dziegielewska-Gesiak, Edyta Fatyga, Teresa Kokot Department of Internal Medicine, Silesian Medical University, Katowice, PolandLapid et al recently published an interesting article in Clinical Interventions in Aging entitled: "Vitamin D and depression in geriatric primary care patients".1 Their conclusion that "lower vitamin D levels were associated with depression" was based on a study that analyzed the patients in primary care internal medicine "who had at least one total serum 25-hydroxyvitamin D [25(OH)D] level from 2004–2008. For those with multiple serum 25(OH)D measurements, authors used the index of first measurements".1View original paper by Lapid and colleagues.